Caracterização e atividade antioxidante da jabuticaba [Myrciaria cauliflora (Mart.) O. Berg] - Lima, Annete de Jesus Boari (2009)
The Jabuticaba tree, [Myrciaria cauliflora (Mart.) O. Berg], is a native plant of Brazil, belonging to Myrtaceae family of which very little is known about the chemical composition of its fruit. In this work, the whole fruit and fractions (skin, pulp and seeds), of two varieties, Paulista and Sabará, were analyzed as to the chemical constituents and the antioxidant activity. The skin and seed together represent approximately 50% of the fruit. Protein and ether extracts were found at low levels in all fractions. Ash content did not vary among fractions, except for the Sabará fruit skin, which presented the highest amount. Dietary fiber differed widely among fractions, with no differences between varieties. Regarding the bioactive compounds, only polyphenols in the skin presented high levels. Pulp fractions presented the highest amounts of total sugar, mainly fructose and glucose followed by sucrose, which are also found in the skin, seed fractions and in the whole fruit. Five organic acids were found in the pulp fractions and in the whole fruit: citric acid > succinic acid > malic acid > oxalic acid > acetic acid. In skins and seeds, the succinic and citric acids appeared as majority acids. The malic and acetic acids are present in very low quantities in all the fractions of both varieties. Larger quantities of vitamin C were found in the skin and seed fractions of both varieties. Among the minerals, potassium was the most abundant element. The amount of iron in the pulp was twice the daily recommended dose for human nutrition. This fruit also showed to be rich in magnesium, phosphorus, calcium, and copper. The seed-fraction oil, characterized by GC-MS chromatography, presents almost the same composition in the skin fractions of both varieties. The majority compound was a non-identified phytosterol, followed by the palmitic, linoleic, oleic acids and squalene. Several solvents were tested for anthocyanic-pigment extraction in order to evaluate the pigment stability, to quantify total anthocyanins, HPLC anthocyanins analysis and antioxidant tests. The best extractability was achieved by the maceration of the sample with 95 % ethanol and/or 50 % ethanol, acidified with HCl 1.5 mol L-1; using a proportion of 1:15 (1g of sample to 15 mL of solvent). The skin fraction showed to be rich in anthocyanins and had the cyaniding-3-glucoside as the principal pigment, followed by delphinidin-3-glucoside, which was also present in pulp fractions. The fruit showed to have antioxidant activity, by the free-radical capture test (ABTS) antioxidant capacity (phosphomolibdenium-test) and delayed-fat oxidation process (β-caroten/linoleic-acid bleaching assay). According to these results the fruit has high antioxidant activity, specially the skins that are rich in polyphenols and anthocyanins. The best correlation occurs between polyphenols and the ABTS test. The study demonstrated that the jabuticaba fractions can be utilized in the food industry as additives, as well as in the cosmetic industry, with possible benefit to consumer health.